Teacher/student interaction: A study of successes with students exhibiting attention deficit/hyperactivity disorder behaviors. - Sedovic, Sheri Lynn. (My University, 2001)
The recorded interviews were analyzed to determine common themes within each group and themes common to two or three of the groups. There were a total of 22, 13, and 13 common themes for the teachers, parents, and students, respectively. Eleven themes were common to both teachers and parents, nine themes were common to both teachers and students, and six themes were common to both parents and students.

On the basis of these results it was concluded that: (1) The practices and attitudes of this sample of teachers positively influenced the success of their AD/HD students. (2) The teachers were able to identify their AD/HD students' needs related to academic and social success in school that are found in the literature. (3) Teachers in this study used a number of specific practices to promote the academic and social success of their AD/HD students. These practices included: (a) Caring Relationship between Teacher and Student; (b) Positive Feedback; (c) Counseling the Student; (d) Good Organization; (e) Not Yelling; (f) Preventive Approach; (g) Clear Expectations; (h) Consistency and Predictability; (i) Many Approaches; (j) Explaining Clearly; (k) Use of Humor.

This study examined practices related to the successful teaching of students diagnosed with Attention-Deficit/Hyperactivity Disorder (AD/HD) in the United States Department of Defense Dependent School System (DoDDS) in the Kaiserslautern School District in Germany. In-depth interviews were conducted with six third through fifth grade teachers who had been identified by school administrators as successfully teaching AD/HD students. Interviews were also held with six of their AD/HD students and with one parent of each of the six children. The interviews sought to determine: (1) teacher influence on AD/HD students, (2) the extent of the teacher's awareness of the AD/HD student's learning needs, and (3) successful teaching strategies used with the AD/HD students.

A total of five themes were found to be common to all three groups: (1) Caring Relationship between Teacher and Student; (2) Positive Feedback; (3) Counseling the Student; (4) Good Organization; (5) Not Yelling.
Keywords: Attention-deficit-disordered children Education.; Education, Curriculum and Instruction.